2013
DOI: 10.1016/j.neuroimage.2013.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric analysis of medial temporal lobe structures in brain development from childhood to adolescence

Abstract: Puberty is an important stage of development as a child's sexual and physical characteristics mature because of hormonal changes. To better understand puberty-related effects on brain development, we investigated the magnetic resonance imaging (MRI) data of 306 subjects from 4 to 18 years of age. Subjects were grouped into before and during puberty groups according to their sexual maturity levels measured by the puberty scores. An appearance model-based automatic segmentation method with patch-based local refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 57 publications
6
102
1
1
Order By: Relevance
“…Sex differences in brain structure are well documented (48,49) and are increasingly tied to developmental effects related to puberty (13,46,(50)(51)(52)(53). In particular, several studies have found that puberty in females and rising estrogen is related to increased gray matter in structures such as the hippocampus (51,52,54) that are known to have high density of gonadotropin receptors (55). Because CBF is higher in gray matter than in white matter, these findings underscore the necessity of accounting for changes in brain structure when modeling developmental changes in CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in brain structure are well documented (48,49) and are increasingly tied to developmental effects related to puberty (13,46,(50)(51)(52)(53). In particular, several studies have found that puberty in females and rising estrogen is related to increased gray matter in structures such as the hippocampus (51,52,54) that are known to have high density of gonadotropin receptors (55). Because CBF is higher in gray matter than in white matter, these findings underscore the necessity of accounting for changes in brain structure when modeling developmental changes in CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Given the aims of the study, only scans that included existing callosal contours (Luders et al, 2010; Luders et al, 2011; Kurth et al, 2012), data on sexual development (Hu et al, 2013), and puberty scores of less than 4—as measured by the Pubertal Development Scale (Petersen et al, 1988)—were included. The Pubertal Developmental Scale has been found to be both valid and reliable in discerning subjects’ pubertal status (Petersen et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Hu et al, for example, linked pubertal status to volumetric changes in medial temporal lobe structures (Hu et al, 2013). Bramen et al addressed puberty effects on medial temporal lobe, thalamic, caudate, and cortical gray matter volumes as well as on cortical thickness (Bramen et al, 2011; Bramen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several magnetic resonance imaging (MRI) studies have investigated age-related differences or longitudinal changes in hippocampal volumes specifically (table 1). It is clear that the hippocampus undergoes growth in childhood [12,13,14], but studies have given varying results concerning the second decade of life: the majority have not found significant effects [13,14,15,16,17], while others have found volume decreases [18] or increases [19]. Importantly, the hippocampus is anatomically and functionally heterogeneous [20], and insufficient spatial resolution may mask regional developmental patterns.…”
Section: Introductionmentioning
confidence: 99%